2006
DOI: 10.1103/physrevb.73.035210
|View full text |Cite
|
Sign up to set email alerts
|

Codoping as a measure against donor deactivation in Si:Ab initiocalculations

Abstract: Based on ab initio calculations, we evaluate the effectiveness of various group I, II, and IV elements as possible codopants in highly n-doped Si. The fabrication of ultrashallow junctions in future silicon technology requires the suppression of donor deactivation and diffusion during the annealing. The main goal is therefore the elimination of excess vacancies, both isolated and in donor-vacancy ͑D n V m ͒ clusters. We find that the isovalent impurities C and Ge are unsuited for the intended purpose of D n V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…74 A possible solution is co-doping with an electrically not active impurity that has a stronger binding with the vacancy than the dopant atom. Ab initio calculations show that co-doping with Ge or C is not effective due to their weak binding with the vacancy 75 as is also apparent from Table III. The calculations also suggest that Mg might be a suitable co-dopant in n-type Si to reduce the vacancy concentration as it shows a strong binding energy with the vacancy and at the same time when complexes are formed has a tendency to act as a donor.…”
Section: Impact Of the Fermi Level On [V/ G0] Cr I Tmentioning
confidence: 86%
“…74 A possible solution is co-doping with an electrically not active impurity that has a stronger binding with the vacancy than the dopant atom. Ab initio calculations show that co-doping with Ge or C is not effective due to their weak binding with the vacancy 75 as is also apparent from Table III. The calculations also suggest that Mg might be a suitable co-dopant in n-type Si to reduce the vacancy concentration as it shows a strong binding energy with the vacancy and at the same time when complexes are formed has a tendency to act as a donor.…”
Section: Impact Of the Fermi Level On [V/ G0] Cr I Tmentioning
confidence: 86%
“…Transistors beyond the 14 nm node will require electrically active dopant concentrations in excess of ∼10 21 cm –3 to maintain performance, far beyond what is currently possible using traditional doping techniques such as ion implantation . The use of two-dimensional doping methods has been suggested as a means to achieve higher active dopant concentrations in a range of materials for ultrashallow junctions, avoiding the formation of deactivating dopant pairs in adjacent crystallographic planes. In particular, monolayer doping of Si has been used to produce high n -type sheet densities in silicon 2DEGs, reaching active carrier densities of (2–3) × 10 14 cm –2 for both Sb and P dopants. , Recently, it has been demonstrated that an optimized double-dosing recipe yields a maximum active carrier density of n s = (3.6 ± 0.1) × 10 14 cm –2 (∼0.5 ML) in a single Si:P δ-layer without the formation of deactivating dopant precipitates .…”
mentioning
confidence: 99%
“…Ab initio calculations reveal that formation of C-As complex has a deactivating effect because the C-As complex is electrically inactive and neutral at high Fermi level. 21 Lower dopant activation in SPE Si:C will offset the performance gain due to strain effect, especially for aggressively scaled n-MOSFETs. This problem can be mitigated with the use of PLA that allows for improved dopant activation in Si:C samples.…”
Section: Resultsmentioning
confidence: 99%